Hand, Foot, and Mouth Disease: A Narrative Review - Leung, Alexander K. C.; Lam, Joseph M.; Barankin, Benjamin; Leong, Kin F.; Hon, Kam Lun (Recent Advances in Inflammation & Allergy Drug Discovery, 2022)
Background: Hand, foot, and mouth disease is a common viral disease in childhood. Because the disease has the potential to reach epidemic levels and mortality is high in some countries, early recognition of this disease is of paramount importance. Objective: This purpose of this article is to familiarize pediatricians with the clinical manifestations and management of hand, foot, and mouth disease. Methods: A search was conducted in February 2022 in PubMed Clinical Queries using the key term
Keywords: onychomadesis